Emerging biopharmaceuticals from bioactive peptides derived from marine organisms. (6th February 2017) - Anjum, Komal; Abbas, Syed Qamar; Akhter, Najeeb; Shagufta, Bibi Ibtesam; Shah, Sayed Asmat Ali; Hassan, Syed Shams ul
Abstract : Biologically active natural products are spontaneous medicinal entrants, which encourage synthetic access for enhancing and supporting drug discovery and development. Marine bioactive peptides are considered as a rich source of natural products that may provide long‐term health, in addition to many prophylactic and curative medicinal drug treatments. The large literature concerning marine peptides has been collected, which shows high potential of nutraceutical and therapeutic efficacy encompassing wide spectra of bioactivities against a number of infection‐causing agents. Their antimicrobial, antimalarial, antitumor, antiviral, and cardioprotective actions have achieved the attention of the pharmaceutical industry toward new design of drug formulations, for treatment and prevention of several infections. However, the mechanism of action of many peptide molecules has been still untapped. So in this regard, this paper reviews several peptide compounds by which they interfere with human pathogenesis. This knowledge is one of the key tools to be understood especially for the biotransformation of biomolecules into targeted medicines. The fact that different diseases have the capability to fight at different sites inside the body can lead to a new wave of increasing the chances to produce targeted medicines. Abstract : Marine peptides are a drug treasure house. Marine peptides are one of the major needs for pharmaceutical and nutraceuticals. The mode of action of every biomolecule is one of the basic tools to be known for transformation of bioactive compound into medicines.